2014
DOI: 10.1016/j.egypro.2014.07.147
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Poly (methyl methacrylate) Microcapsule with Encapsulated Jasmine Oil

Abstract: The microencapsulation of jasmine oil with polymethyl methacrylate (PMMA) was carried out by solvent evaporation method in oil in water (O/W) emulsion system. The oil phase was formed by the mixing of PMMA, jasmine oil and toluene and then dispersed in polyvinyl alcohol solution as stabilizer. After solvent evaporation, PMMA microcapsules with encapsulated jasmine oil were formed. The influence of weight ratio of PMMA:jasmine oil on the preparation of polymer capsule was studied. It was found that using 1:1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…Essential oils have many applications in cosmetic, medicinal, and pesticide components. Encapsulation of volatile essential oils can be useful for controlled release application of them over time . Abdullah et al .…”
Section: Application Of Pmma Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils have many applications in cosmetic, medicinal, and pesticide components. Encapsulation of volatile essential oils can be useful for controlled release application of them over time . Abdullah et al .…”
Section: Application Of Pmma Capsulesmentioning
confidence: 99%
“…The influence of Jasmine oil/PMMA weight ratio was studied. It was found that using Jasmine oil/PMMA of 2:1, the spherical microcapsules with smooth outer surface and high oil content were obtained …”
Section: Application Of Pmma Capsulesmentioning
confidence: 99%
“…Teeka et al . microencapsulated jasmine EOs with polymethyl methacrylate by solvent evaporation method in oil‐in‐water (o/w) emulsion system with an encapsulation efficiency of 72%.…”
Section: Microencapsulation Of Eosmentioning
confidence: 99%
“…The emulsification of the oil phase in the water phase has an important effect on the coating ratio of microcapsules by the solvent evaporation method [24,25]. Therefore, the selection of suitable aqueous emulsifiers is crucial to the successful encapsulation.…”
Section: Resultsmentioning
confidence: 99%